Guidelines for the pharmacological treatment of peripheral neuropathic pain - Riachi, N. (2010)
Neuropathic pain (NeP) has been the focus of extensive basic and clinical research over the past 20 years. This has led to an increased understanding of underlying pathophysiological mechanisms and the development of new therapeutic agents, as well as a clearer definition of the role of established medications. To date there are no published treatment guidelines for NeP in the Middle East. A multidisciplinary panel of Middle East and international experts met to review critically and reach a consensus on how best to apply evidence-based guidelines for the treatment of NeP (mainly peripheral NeP) in the Middle East. The expert panel recommended pregabalin, gabapentin and secondary amine tricyclic antidepressants (nortriptyline and desipramine) as first-line treatments for peripheral NeP. Serotonin-norepinephrine reuptake inhibitor antidepressants, tramadol and controlled-release opioid analgesics were recommended as second-line treatments. There is a need to increase diagnostic awareness of NeP, use validated screening questionnaires and undertake more treatment research in the Middle East region.